Pneumonia in myasthenia gravis: Microbial etiology and clinical management - Su, Manqiqige; Jin, Shan; Jiao, Kexin; Yan, Chong; Song, Jie; Xi, Jianying; Zhao, Chongbo; Zhou, Zhirui; Zheng, Jianming; Luo, Sushan (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Patients with myasthenia gravis (MG) are prone to the development of pneumonia due to the long-term immunotherapies they receive and a tendency for aspiration. Pneumonia remains a risk factor for MG worsening and is the most prevalent cause of mortality in MG patients. Classification of the pathogens involved and exploration of the risk factors for mechanical ventilation (MV) could aid in improving clinical outcomes. Methods Between January 2013 and October 2022, we performed an inpatient database review for MG patients with pneumonia concurrence in a tertiary research center specializing in neuromuscular disorders. The clinical and microbiological characteristics of 116 MG patients with pneumonia were retrospectively analyzed. Results In our cohort, 90.32% (112/124) of organisms were bacteria and 42.86% (48/112) of pathogenic bacteria were carbapenem-resistant. A high abundance of Epstein–Barr virus (EBV) was detected using next-generation sequencing (NGS) in 12 patients, while cytomegalovirus (CMV) was detected in 8 patients. Non-fermentative Gram-negative bacilli were the most prevalent microorganisms, in which ampicillin, sulfamethoxazole-trimethoprim (SMZ-TMP), piperacillin, cefoperazone, ceftazidime, and cefepime may have an anti-infectious effect. Moreover, peripheral lymphocyte percentage [odds ratio (OR) 0.88, 95% CI 0.75–0.96, p = 0.02] and serum globulin (OR 1.16, 95% CI 1.02–1.35, p = 0.03) were significantly associated with the risk of MV demand. Discussion Our identification of the microbial etiology of pneumonia in MG patients may provide future perspectives on accurate antibiotic options and enable early interventions when risk factors are present.